Extending Health Care Coverage to the Low-Income Population: The Influence of the Wisconsin BadgerCare Program on Labor Market Outcomes - Barbara Wolfe; Thomas Kaplan; Robert Haveman; Yoon Young Cho (Institute for the Study of Labor (IZA), 2005)
The Wisconsin BadgerCare program, which became operational in July 1999, expanded public health insurance eligibility to families with incomes below 185 percent of the U.S poverty line (200 percent for those already enrolled). This eligibility expansion was part of a federal initiative known as the State Children?s Health Initiative Program (SCHIP). In this paper, we investigate the effect of Wisconsin?s BadgerCare on the labor market outcomes of low-income single mothers. Using a coordinated set of administrative databases, we track three cohorts of mother-only families: those who were receiving cash assistance under the Wisconsin AFDC and TANF programs in September 1995, 1997, and 1999, and who subsequently left welfare. We follow the 19,201 single mothers heading these ?welfare leaver? families on a quarterly basis from two years before they left welfare through the end of 2001. We use information on the labor market and welfare history of these women and their household characteristics and macroeconomic environment to analyze the effect of the availability of additional public health coverage on their employment and earnings. We apply multiple methods to investigate these outcomes, comparing across- and within-individual differences. The core finding is that labor earnings increased with the introduction of BadgerCare. This increase was small in absolute dollar value but sizeable in percentage terms.
Keywords: J21; I18; 330; health care coverage